“THE HELL OF GALICIAN UKRAINE”: THALERHOF'S IMAGES ON THE PAGES OF THE “NASH LEMKO” NEWSPAPER - NAKONECHNYI, Volodymyr; BENCH, Olga; CHERNYSHOVA, Valeriia (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
The purpose of the study is to clarify the peculiarities of a diverse understanding related to the Thalerhof concentration camp issue by the representatives of the authors' circle of the “Nash Lemko” newspaper. The methodological basis of the research is an interdisciplinary approach. In the article such methods and approaches as systematic, comparative and critical analysis of the source base, represented by large text arrays, have been used. The correct interpretation of various genres of the newspaper information has been made possible by the use of the content analysis method. The scientific novelty of the article consists in the attempt to comprehensively analyse the reception of a number of Thalerhof stories by the authors of the “Nash Lemko” newspaper. In conclusion, it has been noted that it was the Thalerhof events that significantly influenced the self-awareness of the Ruthenians as an ethnic group during the interwar period. Realizing this issue somewhat later than the representatives of the Muscovite camp, the Ruthenian intellectuals united around the “Nash Lemko” newspaper and began a difficult activity of deconstructing the stereotypes spread by their opponents, and thus a difficult activity of Ukrainizing the Thalerhof narrative. The activity carried out by Yulian Tarnovych, Petro Antonyshyn, Ostap Kostarevych and other employees of the newspaper was multifaceted, as it included the development of a new conceptual model, interviewing eyewitnesses of the tragedy, processing and publishing their memories, preparing polemical speeches, writing analytical studies, etc. As a result, a completely competitive historiographical image of the Thalerhof tragedy was created, which encouraged the Lemkos to remain with the Ukrainian national choice after their expulsion from their native lands and a subsequent resettlement by many diaspora centres during the post-war years. This conceptually balanced and factually based interpretative model proved to be in demand for the Ukrainian socio-humanitarian studies of the independence era, becoming an organic component of a modern academic reconstructure of the Thalerhof issue. Keywords: the “Nash Lemko” newspaper, Thalerhof concentration camp, Second Polish-Lithuanian Commonwealth, Muscovite, reception.